Greenland, view of Kjerulf Fjord through to Dicksons Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. Extreme inner end. In background; on left, mts. [mountains] forming west side of Kjerulfs [Kjerulf] Fjord, here seen forming west side of Main Valley, at northern end of this valley. Smoke from the Menzies' fire of Aug. 1st is seen blowing south. In foreground; floor of Main Valley. Photo taken looking N.W. This photo is no. 5 in pan E.